The Association between Immediate Postpartum Depot Medroxyprogesterone Acetate Use and Postpartum Depressive Symptoms - Ross, Carolyn M.; Shim, Jessica Y.; Stark, Elisabeth L.; Wisner, Katherine L.; Miller, Emily S. (American Journal of Perinatology, 2021)
Objective While postpartum depot medroxyprogesterone acetate (DMPA) is a highly effective form of contraception, some data suggest an association with depressive symptoms. Our objective was to evaluate the relationship between receipt of DMPA in the immediate postpartum period and postpartum depressive symptoms.Study Design This retrospective cohort study included all women who received prenatal and postpartum care at academic obstetric clinics affiliated with a tertiary care institution between January 1, 2008 and December 31, 2014. All women were counseled on contraception prior to hospital discharge. DMPA was available in the hospital pharmacy, and its utilization was documented in the electronic health record. The Patient Health Questionnaire 9 (PHQ-9) was used to screen for postpartum depression for all women at all postpartum visits. A score of 10 or greater was categorized as positive. Bivariable and multivariable analyses were used to identify the association between immediate postpartum DMPA use and a positive postpartum depression screen.Results Of the 5,073 women who met inclusion criteria, 410 (8.1%) received DMPA prior to hospital discharge. Compared with women who did not receive DMPA, women who received DMPA prior to hospital discharge were younger, more likely to identify as Black race or Latinx ethnicity, and more likely to be publicly insured. Clinical characteristics also differed. Women who received DMPA were more likely to be obese and to have experienced prenatal depressive symptoms, been diagnosed with a hypertensive disorder of pregnancy, delivered preterm, and delivered vaginally. Receipt of immediate postpartum DMPA was not associated with having a positive screen for postpartum depression in bivariable (5.4 vs. 6.0%, p = 0.29) or multivariable (adjusted odds ratio 0.94, confidence interval 0.53–1.68) analyses.Conclusion Receipt of postpartum DMPA is not associated with a positive postpartum PHQ-9 screen. Concerns about precipitating postpartum depression should not preclude the utilization of DMPA as a contraceptive agent.Key Points
Keywords: postpartum depression; depot medroxyprogesterone acetate (DMPA); progestin; contraception; PHQ-9